Cae design of maca impurity separator machine for improving the dehydration process - Meza Cardenas, Alex Frank (2025)
Over the years, there has been a massive expansion of maca crops in the province of Junín, causing a shortage of skilled labour, which has led to an increase in cost and time in the dehydration process in the production of maca. This is how the main problem arises: How do I design and manufacture a machine to separate impurities from maca to improve the dehydration process? The project is based on the design and manufacture of a device that helps to reduce the time spent in the cleaning area in the dehydration process, as this is where the most time is spent and in turn, generates more costs for skilled labour. It should be noted that this process is carried out manually by two people using mesh sacks, taking an average of 4 minutes per 10 kg of maca. This machinery consists of a metal structure that supports the baskets, whose function is to clean the impurities brought by the maca, which in turn will be driven by an internal combustion engine, regulated by a gearbox. After the analysis and tests carried out on the machine, it was found that the cleaning time of the maca is 34 kg per minute, which is 80% more efficient than the manual process, which takes longer and generates high costs.